Value of Dermoscopy in a Population-Based Screening Sample by Dermatologists - Isabelle Hoorens; Katrien Vossaert; Sven Lanssens; Laurence Dierckxsens; Giuseppe Argenziano; Lieve Brochez (Mattioli1885, 2019)
Background: The use of dermoscopy improves the diagnosis of skin cancer significantly in trained dermatologists. However, to evaluate its cost-effectiveness in daily practice, not only sensitivity but also the excision rate is important. Objective: We examined the diagnostic accuracy of cases from a true population-based sample scored by general dermatologists. Methods: One hundred twenty-six dermatologists were randomly assigned to 145 digital cases of lesions detected at a skin cancer screening. This resulted in 4,655 case evaluations using a web application. Accuracy of diagnosis and treatment was correlated with the histological diagnosis or expert opinion. Results: The larger portion (89.7%) of the participating dermatologists reported using their dermatoscope daily. The odds of making a correct diagnosis of melanoma using dermoscopy was 5.38 compared with naked-eye examination (NEE). Dermoscopy increased sensitivity for skin cancer diagnosis from 70.6% to 84.6%, but this was associated with a small but significant decrease in specificity of 3.5%. To detect 1 skin cancer, 5.23 lesions had to be biopsied/excised in this sample and this was not significantly improved by dermoscopic evaluation. Dermoscopy significantly increased the confidence about making a correct diagnosis, especially in seborrheic keratosis, Bowen disease, and melanoma. Conclusions: Dermoscopy significantly improved diagnostic accuracy, the sensitivity of skin cancer detection, and the confidence in diagnosis especially for seborrheic keratosis, Bowen disease, and melanoma. However, this finding was not reflected in a significant reduction in the number needed to excise in this sample.